2007
DOI: 10.1097/iop.0b013e3181596b68
|View full text |Cite
|
Sign up to set email alerts
|

Benign Reactive Lymphoid Hyperplasia of the Caruncle and Plica: Report of 5 Cases

Abstract: Benign reactive lymphoid hyperplasia should be considered in the differential diagnosis of mass lesions of the caruncle and plica semilunaris, especially in young male patients. Histopathologic evaluation and immunohistochemistry studies are necessary to exclude lymphoma and other malignant lesions. Complete surgical excision of the plica or caruncle does not seem to induce significant complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…Two subjects only 14 years of age and the oldest was 30 years. Three of the subjects were males in accordance with previous reports that suggested higher incidence among males 20. We found very few cases of benign lymphoid hyperplasia affecting children documented in the literature 21.…”
Section: Discussionsupporting
confidence: 91%
“…Two subjects only 14 years of age and the oldest was 30 years. Three of the subjects were males in accordance with previous reports that suggested higher incidence among males 20. We found very few cases of benign lymphoid hyperplasia affecting children documented in the literature 21.…”
Section: Discussionsupporting
confidence: 91%
“…Small mature lymphocytes usually populate the interfollicular zones [4, 6]. These follicles usually present distinct borders, variable size and irregular shape and are divided by wide interfollicular areas with prominent mantle zones [4, 7]. In contrast, neoplastic follicles are more closely packed together, do not vary in size and shape, and their mantle zones may not be evident [4, 7].…”
Section: Discussionmentioning
confidence: 99%
“…These follicles usually present distinct borders, variable size and irregular shape and are divided by wide interfollicular areas with prominent mantle zones [4, 7]. In contrast, neoplastic follicles are more closely packed together, do not vary in size and shape, and their mantle zones may not be evident [4, 7]. Moreover, in the majority of cases, RLH lesions are characterized by polyclonality, as well as the absence of Dutcher bodies and cytologic atypia, nonetheless, these features only favor the diagnosis of the disease and are not pathognomonic [2, 7, 26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 An oedematous enlargement of the latter may result from chronic ocular surface inflammation. 3 A previous study has reported that nasal pterygia are associated with plica semilunaris ectopia, causing 'withthe-rule' corneal astigmatism because of the exertion of tractional forces and thus supported the idea that the ectopia of the plica semilunaris in pterygium is an epiphenomenon rather than a causative association. 4 Motivated by this finding, we examined the size and location of the plica semilunaris in candidates for primary (non-recurrent) nasal pterygium excision (Pterygium Group, PG) and an age-and gender-matched group of cataract surgery candidates (Control Group, CG) with a view to further evaluate the potential role of the plica semilunaris in the clinical profile of ophthalmic pterygium.…”
mentioning
confidence: 85%